Additives to elephant grass ensilage. I. Chemical composition of fodder and silages - de Andrade, João Batista (1998)
The effect of the addition of ground ear corn with husks, wheat bran and saccharin, on the rate of 0, 8, 16 and 24% (dry weight of additive/wet weight of cut green grass), upon the chemical composition of both fodder and silage of Pennisetum purpureum Schum. cv. Guaçu was evaluated. A split-plot randomized block design was used. The plots were the additives and their levels and the sub-plots the material types (forage + additives and their silages). The grass was fertilized with 20 t/ha of green manure and 80, 160 and 160 kg/ha of P2O5, N and K2O, respectively. The material (chopped grass mixed with the levels of the additives) was ensiled in experimental silos (200 L plastic vessels). The dry matter percentages increased linearly as additive levels increased, being greater the effect of ground ear corn with husks. Wheat bran addition and saccharin increased the crude protein and soluble carbohydrates percentages while the ground ear corn with husks addition decreased them. Losses of dry matter soluble compounds (CP, ash and NFE) and a relative rise in the less soluble compounds (CF and organic matter) were observed.